Effectiveness of internal control system over the pay roll: The case of institute of adult education, head office, Dar es salaam - Safari, Ali I. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements of the award of Masters Degree of Business Administration in Corporate Management (MBA-CM) – of Mzumbe University